Net requirements of protein and energy for maintenance of wool and hair lambs in a tropical region - Silva, AMA; Sobrinho, AGD; Trindade, IACM; Resende, Kleber Tomás de [UNESP]; Bakke, O. A. (Elsevier B.V., 2003)
The objective of this work was to evaluate the total endogenous N losses, and protein and energy net requirements for maintenance in growing lambs. Thirty-four castrated lambs, 17 F1 Ideal X Ile de France wool and 17 Santa Inas hair lambs, averaging 20 +/- 0.14 kg BW, were used in the experiment. Five animals from each genotype were slaughtered at the beginning of the experiment and taken as controls. Diets (D) were composed of concentrate mix (C) and Cynodon sp. c.v. Tifton 85 hay (R), combined in three different ratios: D1 = 60C:40R; D2 = 40C:60R and D3 = 20C:80R. Animals of each group of three lambs, that showed BW of 20 kg at the beginning of the dietary regimen, were slaughtered when one of them reached 35 kg, what always happened to be the one fed with D1. Total endogenous N losses estimated for wool lambs were 250 mg N/kg BW0.75. For hair lambs, total endogenous N losses reached 324 mg N/kg BW0.75 . Hair lambs showed higher (P < 0.01) (29.9%) net requirements of protein for maintenance than wool lambs. In contrast, net energy (NE) requirement for maintenance was similar (P > 0.05) for both genotypes (74.27 kcal/kg BW0.75 per day), the average of the antilog of the two intercept values obtained from the estimated regression equations of heat production for zero metabolizable energy (ME) consumption. Further studies should be done to check if this trend is also true for metabolizable energy and protein in animals exhibiting BW gains in tropical region. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: maintenance requirements; endogenous nitrogen; wool lambs; hair lambs